Did the 2003 Tax Act reduce the cost of equity capital? - Dhaliwal, Dan; Krull, Linda; Li, Oliver Zhen (Journal of Accounting and Economics, 2007)
The Jobs and Growth Tax Relief Reconciliation Act of 2003 reduced shareholder-level taxes on equity income. If shareholder-level taxation is a component of cost of equity capital, then the cost of equity capital should decrease after the Tax Act. We find that the cost of equity capital decreases by 1.02% and that the decline is smaller for firms largely held by institutional investors to whom the tax rate reduction does not apply. These results suggest that the Tax Act lowered the cost of equity capital and add further evidence to the question of whether taxes impact valuation.